2022
DOI: 10.1371/journal.pone.0272162
|View full text |Cite
|
Sign up to set email alerts
|

Real world effectiveness of digital mental health services during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic created an unprecedented need for mental health services that can be remotely delivered. Digital mental health services that offer personalized care recommendations hold promise to efficiently expand service, but evidence of the effectiveness of digitally delivered mental health care in real-world settings remains limited. Methods A retrospective cohort of adults (N = 1,852) receiving care through a digital mental health platform with elevated depressive symptoms during the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The results of this study support the existing body of literature showing that digital platforms are a valuable option for filling gaps in mental healthcare ( 10 12 ). Previous research has found a benefit in clinical outcomes and patient-reported well-being and satisfaction for people who leveraged telehealth services ( 21 ). Remotely delivered interventions, such as guided meditation or engaging in behavioral health care, have been shown to help reduce anxiety and improve overall mental health during pregnancy ( 13 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study support the existing body of literature showing that digital platforms are a valuable option for filling gaps in mental healthcare ( 10 12 ). Previous research has found a benefit in clinical outcomes and patient-reported well-being and satisfaction for people who leveraged telehealth services ( 21 ). Remotely delivered interventions, such as guided meditation or engaging in behavioral health care, have been shown to help reduce anxiety and improve overall mental health during pregnancy ( 13 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…DMHIs may improve accessibility, can bridge social gaps, and allow users to log in anonymously whenever they want (Sorkin et al, 2021).Because DMHIs are believed to be an effective tool to address underutilization of professional mental health services (Garrido et al, 2019), several studies assessed their effectiveness. Overall, these studies supported the effectiveness of DMHIs in reducing anxiety and depression symptoms and showed that digital mental health programs can be as effective as in-person programs and sometimes more effective for adults (Cuijpers et al, 2010;Prescott et al, 2022) and children (Pǎsǎrelu et al, 2017). Several reviews of technology applications for mental health found positive outcomes and important benefits (Firth et al, 2017;Garrido et al, 2019).…”
mentioning
confidence: 85%
“…The outcomes and impact of using computer models in real-world settings are still being evaluated, but early studies suggest that they have the potential to improve diagnosis accuracy, enhance cost-effectiveness, personalized treatment and real time monitoring. Real world effectiveness of digital mental health services are also monitored during COVID-19 also [18].…”
Section: Outcomes and Impact Of Using Computer Models In Real-worldmentioning
confidence: 99%